Efectividad de ejercicios de propiocepción con cama elástica en pacientes con inestabilidad de tobillo que practican kickboxing - Ortiz Bautista, Gabriela Alexandra (2017)
Introduction: The ankle joint also known as the talocrural region is made up of the most distal and malleolar area of the lower limb. The ankle joint with the foot, provides a support structure for body weight in the standing position and in the function of the locomotor apparatus. Within injuries involving the tibioperoneal astragalin joint, they are found in 78 percent of sprains, occurring in 1 per 10,000 people each day. A global incidence of 30 percent of the people who perform the sport where the most common mechanism of injury is the investment, once the proprioceptive system is affected which is indispensable to properly locate the gesture that we want to perform in time and the space that is complementary to this system to maintain joint stability in both static and dynamic, facilitating control and the correct location of movement in people who practice recreational Kickboxing. Objective: Analyze the effectiveness of elastic bed exercises in patients with ankle instability who practice kickboxing. Materials and methods: In the study, 10 subjects who were kickboxing practitioners, women and men, between the ages of 18 and 35 years, who had a diagnosis confirmed by the specialist of ankle instability, were recruited. The subjects evaluated were divided into two groups of 5 members. 5 subjects belong to the control group, who performed proprioceptive exercises with elastic bed and the remaining 5 were the control group who performed proprioceptive exercises without elastic bed. For data collection using the JAMA dynamometer by measuring the maximum force peak in the subject is work, also to determine the number of actions and the load exerted before a jump and the jump output in a range of 10 seconds later were used for analysis in the COBS Platform in this way balance and coordination in the ankle, so it was retaken the measures after the treatment quantifying the findings in the final phase of the study. The treatment was performed in a time of 3 weeks with a total of 12 sessions with a duration of 20 minutes each, leaving an interval between them. The evaluation was at the beginning and at the end of the treatment. In the experimental group, proprioceptive exercises with elastic bed were applied during 12 sessions; While the control group is applied to the same proprioceptive exercises without the use of the elastic bed. Results: Significant differences were found in intergroup relations between GC-D and GC-I. Demonstrating that prior to treatment…see attached file.